2001
DOI: 10.1063/1.1396679
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the molten BeF2 viscosity anomaly in terms of a high temperature density maximum, and other waterlike features

Abstract: In an effort to understand the anomalous behavior of the viscosity of liquid beryllium fluoride relative to other liquids in the strong/fragile classification we have carried out ion dynamics computer simulations of BeF2 over a temperature range which overlaps with the experimental viscosity data. Using the simple rigid ion potentials which seem to be suitable for the nonpolarizable ions of this substance, we obtain diffusivity data which are in good agreement with values obtained from the experimental viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 59 publications
(48 reference statements)
8
87
0
Order By: Relevance
“…4 shows that indeed, numerical data for C conf V display a peak at T ≈ 0.25. A peak in C conf V (T ) has also been observed in recent simulations of atomistic models of two different network-forming liquids: silica [31] and BeF 2 [65].…”
Section: B) Energy Landscapementioning
confidence: 72%
“…4 shows that indeed, numerical data for C conf V display a peak at T ≈ 0.25. A peak in C conf V (T ) has also been observed in recent simulations of atomistic models of two different network-forming liquids: silica [31] and BeF 2 [65].…”
Section: B) Energy Landscapementioning
confidence: 72%
“…Saika-Voivod et al 7 revealed a fragile-to-strong transition associated with a heat capacity anomaly above the melting temperature T m by studying static and dynamic properties of liquid silica using numerical simulations. Analogous to SiO 2 , molten BeF 2 studied by Hemmati et al 8 using the ion dynamics simulations exhibits, also, a fragileto-strong crossover as a result of a heat capacity maximum above T m . The experiments available for measuring the heat capacity maximum were carried out by Oguni and co-workers 17,49 using the supercooled water confined within silica gel nanopores to avoid crystallization.…”
Section: Discussionmentioning
confidence: 99%
“…In analogy to water, heat capacity maxima have been also found at high temperature far above the melting point in simulations of the network glassforming liquids SiO 2 (refs 6,7,18) and BeF 2 (refs 8,18). More interestingly, the suggested transitions in these systems are found to relate to an anomalous change in dynamic properties of liquids, known as a strong-fragile crossover or transition 7,8,15,19,20 . This refers to a drastic change in the temperature dependence of relaxation processes (for example, viscosity) between an Arrhenius-like (strong) and a nonArrhenius (fragile) behaviour.…”
mentioning
confidence: 99%
“…oride [62]. It is obvious that the fragile-to-strong transition cannot be framed within the possibility described in the first paragraph of this section.…”
Section: Strong-to-fragile Transitionmentioning
confidence: 98%